Assessment of Human Capital Management (HCM) Implementation and Its Effect on Innovation: Case Study at PT Dirgantara Indonesia - Natanael, Wesley; Ghazali, Achmad; Febriansyah, Hary (The Indonesian Journal of Business Administration, 2014)
Abstract. The financial crisis in 1998 requires the state to stop its funding to PT DI. Lack of funds forced PT DI to cut its employees in large numbers in order to sustain the company survival with business turbulence encountered. This massive layoff was followed by experts skill left the company. This condition raises some problems for companies which are lack of expertise, employees age gap and based on previous research there is still a lack of trust in leaders. Improvement of Human Capital Management (HCM) is required considering problems faced is about human resource management, and must be conducted effectively and accurately targeted because of PT DI limited funds. HCM framework used in this study is framework developed by Laurie Bassi and Daniel McMurrer (2007) which states there are five drive (driver) HCM which are leadership, engagement, knowledge accessibility, workforce optimization dan learning capacity. Assessment of HCM implementation in PT DI using questionnaire tool shows that implementation of HCM in PT DI is still at low level and the driver with the lowest score is Engagement. Innovation used as the expected result because PT DI as aircraft manufacturing company is intense company with innovation. HCM correlation analysis with company innovation capability is conducted by Partial Least Square (PLS) using software smartPLS 2.0. PLS analysis generates that Engagement is the driver with the highest correlation to innovation. The series result of research steps indicate that the Engagement is the driver with the highest correlation to the level of innovation as well has the lowest value of implementation level, so that the increase in HCM should be concentrated on the driver Engagement. In this study, the researcher recommends enhancement Engagement with conduct performance management.Keywords: Human Capital Management (HCM), Innovation, PT Dirgantara Indonesia